The philosophy of Sarvepalli Radhakrishnan - Schilpp, Paul Arthur, 1897-1993. (New York : Tudor Pub. Co., 1952)
Collection of descriptive and critical essays on the philosophy of Radhakrishnan.
Includes bibliographical references and index.
Microfilm.
Keywords: Radhakrishnan, S. -- 1888-1975 -- Philosophy